CORRUPTION AS A SOURCE OF FUNDS FOR MONEY LAUNDERING: LEGAL MECHANISMS OF COUNTERACTION - Banakh, Serhiy; Holota, Nataliia (Актуальні проблеми правознавства, 2025)
The article focuses on the examination of the relationship between corrupt acts and money laundering within the context of current trends in international and national legislation development. The inseparable bidirectional nature of the connection between these phenomena is substantiated, where corruption serves both as a source of illegal proceeds that require legalization and as an instrument for ensuring the functioning of money laundering schemes. It is proven that legal doctrine and practice increasingly emphasize the need to consider these phenomena as interrelated within a unified counteraction strategy, since traditional isolated approaches prove to be insufficiently effective in combating modern complex financial schemes.A comprehensive analysis of key legislative innovations of recent years has been conducted, including the adoption in the USA of the Foreign Extortion Prevention Act (FEPA) 2023, the Anti-Money Laundering Act 2020, China's three-year action plan for combating money laundering (2022‒2024), and the new European regulation on establishing the Authority for Anti-Money Laundering and Countering the Financing of Terrorism. Particular attention is paid to analyzing the impact of these legislative changes on expanding the range of predicate crimes and creating new legal mechanisms for international cooperation. The role of international organizations, particularly FATF, in forming global standards for combating financial crimes and the significance of the Warsaw Convention 2005 and the UN Convention against Corruption (UNCAC) as fundamental international instruments are examinedThe process of adapting Ukrainian legislation to international standards through an analysis of the system of normative legal acts regulating issues of combating corruption and money laundering has been studied. It is proven that Ukraine has formed a comprehensive multilevel architecture of legal regulation that encompasses preventive measures, financial monitoring, and criminal prosecution, ensuring a synergistic effect in combating the legalization of corrupt proceeds and approximation to international standards in this field. A tendency toward convergence of anti-corruption legislation and normative legal regulation of prevention and counteraction to money laundering at the global level has been identified, which reflects the international community's awareness of the systemic nature of these threats to financial stability and economic security.